Does the hepatitis B antigen HBx promote the appearance of liver cancer stem cells? - Arzumanyan, Alla (2011)
Hepatitis B virus (HBV) is a major etiologic agent of chronic liver disease (CLD) and hepatocellular carcinoma (HCC). HBV encoded X antigen, HBx, and pathways implicated in the self-renewal of stem cells contribute to HCC, but it is not clear whether HBx expression promotes “stemness.” Thus, experiments were designed to test the hypothesis that HBx triggers malignant transformation by promoting properties that are characteristic of cancer stem cells (CSCs). To test this hypothesis, HepG2 cells were stably transduced with HBx and then assayed for phenotypic and molecular characteristics of “stemness.” The relationship between HBx and “stemness”-associated markers was also evaluated by immunohistochemical staining of liver and tumor tissue sections from HBV infected patients. The results showed that Oct-4, Nanog, Klf4, β-catenin and EpCAM were activated by HBx in vitro and in vivo. EpCAM was detected in the nuclei of human HCC cells from infected patients. HBx promotes “stemness” by activating β-catenin and epigenetic up-regulation of miR-181, both of which target EpCAM. HBx expression was also associated with depressed levels of E-cadherin. Moreover, HBx stimulated cell migration, growth in soft agar, and spheroid formation. This work is the first to propose that HBV promotes “stemness” in the pathogenesis of HCC. HBx associated up-regulated expression of multiple “stemness” markers support the hypothesis that HBx contributes to hepatocarcinogenesis, at least in part, by promoting changes in gene expression that are characteristics of CSCs.